The Philippines at the crossroads resource curse vs. sustainable development - Arsenio, Balisacan; Ravago, Majah-Leah; Roumasset, James (2010)
Macroeconomic patterns of specialization in the course of sustainable development are illustrated by the coevolution of industrialization ala the flying geese metaphor. A few times in the course of its development, the Philippines has been poised to advance to the middle tier of the V-formation only to find itself sliding to the tail. Such is the pattern of the country's economic development that it is recognized as one of the world's major development conundrums. The paper raises the questions, "Is the country suffering from a curse?" and "What is the source?" In this paper, the authors take the perspective of the resource curse in reviewing unsustainable development practices, and investigate the disease that keeps the Philippines from living up to its potential. they show how the curse does not require the traditional resource boom but can also be promulgated by foreign aid, other forces such as the boom in foreign direct investment during the 1990s economic stagnation in the Philippines. This, alongside with increasing population, exerts undue pressure on environmentally fragile areas. The three pillars of sustainability are proposed as a cure for these pills. The paper concludes by exploring ways how the Dutch disease can be transformed into growth and how development, specialization, and innovation can spur growth and, thus, attain positive sustainability. The Philippine experience teaches all to heed one of the oldest lessons in economics: do not dictate, facilitate.
Keywords: Sustainable development; Rent seeking; Foreign investments